A whole‐genome scan for Artemisinin cytotoxicity reveals a novel therapy for human brain tumors. Issue 3 (6th February 2023) - Taubenschmid‐Stowers, Jasmin; Orthofer, Michael; Laemmerer, Anna; Krauditsch, Christian; Rózsová, Marianna; Studer, Christian; Lötsch, Daniela; Gojo, Johannes; Gabler, Lisa; Dyczynski, Matheus; Efferth, Thomas; Hagelkruys, Astrid; et al.
Abstract: The natural compound Artemisinin is the most widely used antimalarial drug worldwide. Based on its cytotoxicity, it is also used for anticancer therapy. Artemisinin and its derivates are endoperoxides that damage proteins in eukaryotic cells; their definite mechanism of action and host cell targets, however, have remained largely elusive. Using yeast and haploid stem cell screening, we demonstrate that a single cellular pathway, namely porphyrin (heme) biosynthesis, is required for the cytotoxicity of Artemisinins. Genetic or pharmacological modulation of porphyrin production is sufficient to alter its cytotoxicity in eukaryotic cells. Using multiple model systems of human brain tumor development, such as cerebral glioblastoma organoids, and patient‐derived tumor spheroids, we sensitize cancer cells to dihydroartemisinin using the clinically approved porphyrin enhancer and surgical fluorescence marker 5‐aminolevulinic acid, 5‐ALA. A combination treatment of Artemisinins and 5‐ALA markedly and specifically killed brain tumor cells in all model systems tested, including orthotopic patient‐derived xenografts in vivo . These data uncover the critical molecular pathway for Artemisinin cytotoxicity and a sensitization strategy to treat different brain tumors, including drug‐resistant human glioblastomas. Synopsis: Artemisinin requires cellular heme for its cytotoxic function. Its cytotoxicity can be increased by the porphyrin enhancer 5‐ALA, which accumulates in cancer cells. 5‐ALA sensitizes tumor cell. Haploid yeast and mouse ESC genetic screens identify porphyrin production as essential for Artemisinin's cytotoxicity. Ablation of mitochondrial heme/porphyrin biosynthesis increases resistance of cells to Artemisinin derivatives; elevating heme production leads to sensitization. The metabolite 5‐ALA induces porphyrin synthesis and thereby sensitizes cancer cells to Artemisinin killing. Abstract : Artemisinin requires cellular heme for its cytotoxic function. Its cytotoxicity can be increased by the porphyrin enhancer 5‐ALA, which accumulates in cancer cells. 5‐ALA sensitizes tumor cell.